Do insects as feed ingredient affect meat quality? - A. Dalle Zotte (Теория и практика переработки мяса)
The development of sustainable feed ingredients for monogastric livestock is nowadays considering insect meals and oils to replace or supplement conventional feedstuffs. Although the regulation on the use of insect products differs among  countries resulting in restrictions on use in the diets of  monogastric meat producers, global research is exploring all the  strengths and weaknesses of their inclusion. Therefore, whereas  the scientific literature has extensively studied both the  relationship between insect farming systems and safety (potential health risks), and between the dietary use of insects  and the nutritional value of diets and production performance of farm animals (fish, poultry, swine, rabbit), the relationship  between insect-containing diet and meat quality has only recently been considered. The present review therefore aims to  collect the results of the studies that have related the dietary use of some insect species, such as the black soldier fly (Hermetia  illucens), the yellow mealworm (Tenebrio molitor) and the silkworm (Bombyx mori), on the physicochemical and sensory  traits of the poultry, swine and rabbit meat. The variable that has been most affected by the inclusion of insects as feed on  livestock meat quality is the fatty acid (FA) profile, which, as is well known, in monogastrics tends to reflect that of the diet.  Therefore, the black soldier fly inclusion has always originated meats with a more saturated FA profile, the yellow mealworm a  more monounsaturated fatty acid profile, whereas the silkworm a more unsaturated fatty acid profile and rich of valuable  omega-3 FA, but rarely changed the related physicochemical  variables, or the sensory profile of the meat.